Room-temperature larger-scale highly ordered nanorod imprints of ZnO film - Kyaw, Zabu (2015)
Room-temperature large-scale highly ordered nanorod-patterned ZnO films directly integrated on III-nitride light-emitting diodes (LEDs) are proposed and demonstrated via low-cost modified nanoimprinting, avoiding a high-temperature process. with a 600 nm pitch on top of a critical 200 nm thick Imprinting ZnO nanorods of 200 nm in diameter and 200 nm in height continuous ZnO wetting layer, the light output power of the resulting integrated ZnO-nanorod-film/semi-transparent metal/GaN/InGaN LED shows a two-fold enhancement (100% light extraction efficiency improvement) at the injection current of 150 mA, in comparison with the conventional LED without the imprint film. The increased optical output is well explained by the enhanced light scattering and outcoupling of the ZnO-rod structures along with the wetting film, as verified by the numerical simulations. The wetting layer is found to be essential for better impedance matching. The current-voltage characteristics and electroluminescence measurements confirm that there is no noticeable change in the electrical or spectral properties of the final LEDs after ZnO-nanorod film integration. These results suggest that the low-cost high-quality large-scale ZnO-nanorod imprints hold great promise for superior LED light extraction.